Francisella Tularensis Blue–Gray Phase Variation Involves Structural Modifications of Lipopolysaccharide O-Antigen, Core and Lipid A and Affects Intramacrophage Survival and Vaccine Efficacy - Soni, Shilpa; Ernst, Robert; Muszynski, Artur; Mohapatra, Nrusingh P.; Perry, Malcolm B.; Vinogradov, Evgeny; Carlson, Russell W.; Gunn, John S. (Frontiers in Microbiology, 2010)
Francisella tularensis is a CDC Category A biological agent and a potential bioterrorist threat. There is no licensed vaccine against tularemia in the United States. A long-standing issue with potential Francisella vaccines is strain phase variation to a gray form that lacks protective capability in animal models. Comparisons of the parental strain (LVS) and a gray variant (LVSG) have identified lipopolysaccharide (LPS) alterations as a primary change. The LPS of the F. tularensis variant strain gains reactivity to F. novicida anti-LPS antibodies, suggesting structural alterations to the O-antigen. However, biochemical and structural analysis of the F. tularensis LVSG and LVS LPS demonstrated that LVSG has less O-antigen but no major O-antigen structural alterations. Additionally, LVSG possesses structural differences in both the core and lipid A regions, the latter being decreased galactosamine modification. Recent work has identified two genes important in adding galactosamine (flmF2 and flmK) to the lipid A. Quantitative real-time PCR showed reduced transcripts of both of these genes in the gray variant when compared to LVS. Loss of flmF2 or flmK caused less frequent phase conversion but did not alter intramacrophage survival or colony morphology. The LVSG strain demonstrated an intramacrophage survival defect in human and rat but not mouse macrophages. Consistent with this result, the LVSG variant demonstrated little change in LD50 in the mouse model of infection. Furthermore, the LVSG strain lacks the protective capacity of F. tularensis LVS against virulent Type A challenge. These data suggest that the LPS of the F. tularensis LVSG phase variant is dramatically altered. Understanding the mechanism of blue to gray phase variation may lead to a way to inhibit this variation, thus making future F. tularensis vaccines more stable and efficacious.